Analisis Kemampuan Representasi Matematis Untuk Meningkatkan Hasil Belajar Matematika Siswa SMA - Indah Juli Syaputri; Selvia Erita (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to describe the mathematical representation abilities of class X,this research is a qualitative descriptive type research. The subjects in this research were class XII students at SMAN. 2 Kerinci for the 2023/2024 academic year as many as 24 students. The focus of this research is the ability to visual representation, symbolic representation and verbal representation. The research methodology used is qualitative descriptive where tests and documentation are the data collection techniques used. The conclusion of this research is that mathematical representation skills are very important for students to master in determining the right strategy to solve a mathematical problem. Mathematical problems in everyday life, visual, verbal and symbolic representation skills are used, because everyday life problems need to be represented in the form of symbols or images in order to make it easier to solve and face problems.